Survey of the pattern of antibiotic dispensing in private pharmacies in Nepal - Delia Hendrie; Suzanne Robinson; Anant Nepal; Linda A Selvey (BMJ Open)
Objectives Private pharmacies are widely established in most low/middle-income countries (LMICs) including Nepal, and are often considered as a patient’s first point of contact for seeking healthcare. The aim of this study was to investigate the pattern of antibiotic dispensing in private pharmacies through exit interviews with patients to review their medication information.Design and setting Cross-sectional study. Data collection was carried out in 60 days at 33 randomly selected private pharmacies in the Rupandehi district of Nepal.Participants Patients attending private pharmacies (n=1537).Main outcome measure The pattern of antibiotic prescribing and dispensing was investigated using WHO’s core prescribing indicator, ‘the percentage of patients prescribed an antibiotic’. Frequency distributions were presented based on patients’ characteristics, sources of antibiotic, registration status of pharmacies and education of the pharmacist or drug retailer, and disease or condition. χ2 tests and regression analysis were applied to explore factors associated with the pattern of antibiotic dispensing.Results Of patients attending private pharmacies, the proportion receiving at least one antibiotic (38.4%) was above the WHO recommended value (20.0%–26.8%). The most commonly dispensed antibiotics were cefixime (16.9%) and the third-generation cephalosporins (38.0%) class. High dispensing rates of antibiotics for selected conditions (eg, respiratory infections, diarrhoeal cases) appeared contrary to international recommendations. The percentage of antibiotic dispensed was highest for patients who obtained their medicines from unlicensed pharmacies (59.1%). Young people were more likely to receive antibiotics than other age groups.Conclusions The antibiotic dispensing pattern from private pharmacies in Nepal was high compared with WHO guidelines, suggesting initiatives to reduce inappropriate use of antibiotics should be implemented. The findings of this study may be generalisable to other LMICs in order to assist in developing policies and guidelines to promote more appropriate dispensing and prescribing practices of antibiotics and limit the spread of antibiotic resistance.